Analisis Nilai-Nilai Pendidikan Islam pada Buku The Great Prophet Muhammad untuk Pembelajaran SKI di Madrasah Ibtidaiyah - Nisrina Roihanah Zakiyah Nur Imansyah; Dadan F. Ramdhan; Inne Marthyane Pratiwi (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2022)
ABSTRACT (ENGLISH) Given the importance of increasing confidence to Allah Swt to establish a good personality early on by instilling the value of islamic education in learners. Because of that This study aims to expresent the value of islamic education embodied in the book the great prophet muhammad and its relevance to the eye of learning of islamic culture. Because of that, This study aims to expresent the value of islamic education embodied in the book the great prophet muhammad and its relevance to the eye of learning of islamic culture. Research methods used in data analysis by labour-study methods and descriptive qualitative approaches. Data collection techniques use the study of documentation: written sources, pictures, scientific works relating to research and can provide information for the research process. The data analysis techniques used are three stages: data reduction, data presentation, and deduction drawing. Based on research found the value of islamic education in the book the great prophet muhammad for the value of akidah: faith in god and faith in prophets and apostles, the value of worship: conscience, works of the heart, prayer, shadaqah, treasure, observance of amaliah, and moral value: shunning actions of god SWT: the apostle of god brings truth, morality to the prophet: Love and love each other. Chastity to ourselves: honesty, hard work, forgiveness, leadership, philanthropy, thoughtful, affectionate others, not puffed up, not interrupting others' talk, and a good listener. The relevance of the educational values of Islam with the study of the history of islamic culture on the book the great prophet muhammad's value of worship, moral value, acidah value in 3rd and 4th grades. ABSTRAK (INDONESIA) Mengingat pentingnya meningkatkan rasa kepercayaan diri kepada Allah Swt untuk membentuk kepribadian yang baik sejak dini dengan menanamkan nilai-nilai pendidikan Islam pada diri peserta didik. Karena itu penelitian ini bertujuan untuk memaparkan nilai-nilai pendidikan Islam yang terdapat pada buku The Great Prophet Muhammad dan relevansinya terhadap pembelajaran Sejarah Kebudayaan Islam. Metode penelitian yang digunakan dalam analisis data dengan menunggunakan metode penelitian studi kepustakaan dan pendekatan kualitatif deskriptif. Teknik pengumpulan data menggunakan studi dokumentasi: sumber tertulis, gambar, karya ilmiah yang berkaitan dengan penelitian dan dapat memberikan informasi untuk proses penelitian. Teknik analisis data yang digunakan ada tiga tahap: reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan hasil penelitian ditemukan nilai-nilai pendidikan Islam dalam buku The Great Prophet Muhammad yaitu nilai akidah: Iman kepada Allah dan Iman kepada Nabi dan Rasul, nilai ibadah (syariah): ucapan hati, perbuatan hati, shalat, shadaqah, harta, mengamalkan amaliyah, dan nilai akhlak: akhlak terhadap Allah Swt: menghindari perbuatan maksiat, bertakwa, akhlak terhadap Rasulullah: meyakini bahwa Rasul Allah membawa kebenaran, akhlak terhadap orang tua: saling menyayangi dan mencintai sesama keluarga.akhlak terhadap diri sendiri: jujur, berkerja keras, amanah, pemaaf, pemimpin, dermawan, bijaksana, menyayangi orang lain, tidak sombong, tidak memotong pembicaraan orang lain, dan pendengar yang baik. Relevansi nilai-nilai pendidikan Islam dengan pembelajaran Sejarah Kebudayaan Islam pada buku The Great Prophet Muhammad nilai ibadah, nilai akhlak, nilai akidah di jenjang kelas 3 dan 4.